Delusion formation and reasoning biases in those at clinical high risk for psychosis. - Broome, MR; Johns, L; Valli, I; Woolley, J; Tabraham, P; Brett, C; Valmaggia, L; Peters, E; Garety, P; McGuire, P (2007)
BACKGROUND: Cognitive models propose that faulty appraisal of anomalous experiences is critical in developing psychosis, particularly delusions. A data gathering bias may be fundamental to abnormal appraisal. AIMS: To examine whether there is a data gathering bias in people at high risk of developing psychosis. METHOD: Individuals with an at-risk mental state (n=35) were compared with a matched group of healthy volunteers (n=23). Participants were tested using a modified version of the 'beads' reasoning task with different levels of task difficulty. RESULTS: When task demands were high, the at-risk group made judgements on the basis of less information than the control group (P<0.05). Within both groups, jumping to conclusions was directly correlated with the severity of abnormal beliefs and intolerance of uncertainty (P<0.05). In the at-risk group it was also associated with impaired working memory (P<0.05), whereas in the control group poor working memory was associated with a more conservative response style (P<0.05). CONCLUSIONS: People with an at-risk mental state display a jumping to conclusions reasoning style, associated with impaired working memory and intolerance of uncertainty. This may underlie a tendency to develop abnormal beliefs and a vulnerability to psychosis.